2007
DOI: 10.1200/jco.2006.09.3047
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Bevacizumab and Erlotinib in Carcinomas of Unknown Primary Site: The Minnie Pearl Cancer Research Network

Abstract: The combination of bevacizumab and erlotinib has substantial activity in the treatment of patients with CUP. The median survival is superior to survival previously reported with second-line chemotherapy, and is similar to the results of many first-line chemotherapy trials in this setting. This regimen merits further evaluation in patients with CUP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(44 citation statements)
references
References 20 publications
(4 reference statements)
0
41
1
2
Order By: Relevance
“…Recent data have shown that for EGFR inhibitors -at least in colorectal and lung cancer -the mutational status of k-ras is a strong predictor of response efficacy (Linardou et al, 2008) which may apply to CUP, too. A recent pilot study combining bevacizumab and erlotinib in heterogeneous patients has shown considerable efficacy in CUP with a median overall survival of 7.4 months and 33% of patients alive at 1 year (Hainsworth et al, 2007). A high level of EGFR expression of 66% was observed in another study, with EGFR-expressing patients responding considerably better to platinum-based therapy (Massard et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…Recent data have shown that for EGFR inhibitors -at least in colorectal and lung cancer -the mutational status of k-ras is a strong predictor of response efficacy (Linardou et al, 2008) which may apply to CUP, too. A recent pilot study combining bevacizumab and erlotinib in heterogeneous patients has shown considerable efficacy in CUP with a median overall survival of 7.4 months and 33% of patients alive at 1 year (Hainsworth et al, 2007). A high level of EGFR expression of 66% was observed in another study, with EGFR-expressing patients responding considerably better to platinum-based therapy (Massard et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, VEGF blockade appears to prevent the development of resistance to EGFR inhibition [24]. Clinically, the combination of bevacizumab and erlotinib is well tolerated and it has shown activity in several malignancies [9,25,26]. We chose to incorporate agents inhibiting both the VEGF and EGFR pathways based on our previous demonstration of the activity of the bevacizumab-erlotinib combination in the second-line treatment of CUP patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…Because three of these four primary sites are among the most commonly identified at autopsy in patients with CUP [8], it seems likely that these targets are also pertinent in the empiric treatment of patients with CUP. In a previous trial, we investigated the combination of bevacizumab with erlotinib, primarily as a second-line treatment [9]. This combination had substantial activity: 71% of patients were progression free at first re-evaluation, and the median survival duration for this group of previously treated patients was 7.4 months.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The combination of bevacizumab and erlotinib has also been studied in the second-line setting. 18 Although the major response rate with this combination was also low (10%), this regimen appeared to have better activity in producing a median PFS of 4 months and a median overall survival Figure 1. Progression-free survival is shown.…”
Section: Discussionmentioning
confidence: 97%